PENGEMBANGAN MEDIA PEMBELAJARAN GAMBAR BERSERI UNTUK MENINGKATKAN KETERAMPILAN MENULIS NARASI PADA MATA PELAJARAN BAHASA INDONESIA KELAS V SEKOLAH DASAR - Zuraidah Al Fakhiroh, Zulfa; Misbah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is motivated by the limitations of the use of learning resources in delivering material and teachers have not developed learning media that can help in learning so that students do not have an interest in writing, find it difficult to compose sentences, and are unable to express ideas and ideas in the form of narrative writing properly and correctly. This research aims to develop a series of picture learning media to improve students' narrative writing skills in Indonesian Language subjects. This research uses the Research and Development (R&D) method using the ADDIE model which consists of five stages, namely analysis, design, development, implementation and evaluation. The results of the study showed that the serial image media was declared